Optimization Models for The Shelf Space Allocation Problem with Vertical Position Effects - Kateryna CZERNIACHOWSKA; Marcin HERNES (Communications of International Proceedings, 2020)
Shelf space allocation is one of the most important processes in retail management. It influences not only this process performance and costs but also the quality of relationships with customers and customers’ satisfaction. The shelves on which products are displayed in retail stores are some of the most critical resources in the retail environment. The category management and shelf space allocation decisions are therefore issues very important to the retail industry. The objective of this paper is to develop a practical shelf space allocation models with vertical position effects to compare retailers' profit, considering it as linear and non-linear with space elasticity parameters. A comparison of the developed models is also presented. Results obtained from experimental data sets using the CPLEX solver show a significant difference between these solutions.
Keywords: Merchandising; Planogram; Retailing; Shelf Space Allocation; Solver.